Emotional arousal impairs association-memory: roles of amygdala and hippocampus - Madan, Christopher R.; Fujiwara, Esther; Caplan, Jeremy B.; Sommer, Tobias (Elsevier, 2017)
Emotional arousal is well-known to enhance memory for individual items or events, whereas it can impair association memory. The neural mechanism of this association memory impairment by emotion is not known: In response to emotionally arousing information, amygdala activity may interfere with hippocampal associative encoding (e.g., via prefrontal cortex). Alternatively, emotional information may be harder to unitize, resulting in reduced availability of extra-hippocampal medial temporal lobe support for emotional than neutral associations. To test these opposing hypotheses, we compared neural processes underlying successful and unsuccessful encoding of emotional and neutral associations. Participants intentionally studied pairs of neutral and negative pictures (Experiments 1–3). We found reduced association-memory for negative pictures in all experiments, accompanied by item-memory increases in Experiment 2. High-resolution fMRI (Experiment 3) indicated that reductions in associative encoding of emotional information are localizable to an area in ventral-lateral amygdala, driven by attentional/salience effects in the central amygdala. Hippocampal activity was similar during both pair types, but a left hippocampal cluster related to successful encoding was observed only for negative pairs. Extra-hippocampal associative memory processes (e.g., unitization) were more effective for neutral than emotional materials. Our findings suggest that reduced emotional association memory is accompanied by increases in activity and functional coupling within the amygdala. This did not disrupt hippocampal association-memory processes, which indeed were critical for successful emotional association memory formation.